Recovery of the biological active compounds of Musa Sp. through microwave assisted extraction - Farhan, Mohd Said; Tan, Kai Quan (IIUM, 2017)
This study set out to investigate the recovery of the biological active compounds of Musa sp. through microwave-assisted extraction (MAE) system. The aim of this paper is to critically analyze the effects of temperature, microwave power, irradiation time, and solid to liquid ratio on antioxidant activity and phenolic compounds. The extraction was conducted on the unripe peel, unripe pulp, ripe peel, and ripe pulp of Musa sp. The extraction process was carried out by utilizing distilled water as an extracting agent. The antioxidant activity and phenolic compounds for unripe and ripe Musa sp were observed to be extracted best at 70 oC, microwave power range of 500 W – 800 W, and 90 s irradiation time at 3:60 solid to liquid ratio. Overall, antioxidant and phenolic compounds were found to be significantly higher in the following order: unripe peel, ripe peel, unripe pulp, and ripe pulp.